Tantangan Pendiddikan Islam di Era Revolusi Industri 4.0 - Abdurahman Jemani; M. Afif Zamroni (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
Islamic education needs to transform various kinds of core policies in the body of Islamic education itself which are considered capable of answering the challenges and demands. Islamic education in the face of the Industrial Revolution Era 4.0 is expected to be able to bring a positive impact in all walks of life of society, religion, nation and state, not least in the field of Islamic education itself. The era of revolution 4.0 has been able to give birth to a new phenomenon that is considered very disruption so that it demands the world of Islamic education to innovate and become competent competitors. The reality that is happening now, graduates of Islamic education are now faced with new challenges, demands, and needs that are different from previous generations. So it needs to be carried innovations to the system, governance, curriculum, human resource competencies, facilities and infrastructure, culture, work ethic, commitment to change, etc. These things need to be done and get special attention by policy makers in Islamic education. If this is ignored, then Islamic education will be crushed, increasingly left behind and abandoned by its followers. Therefore, concrete steps are needed for Islamic education to be able to remain competitive in this era of disruption. The solutive step offered is to be able to integrate and keep up with changes and developments in technology today for the realization of modern Islamic education and global competitiveness.